Basic ammonothermal growth of Gallium Nitride – State of the art, challenges, perspectives. Issue 3 (September 2018) - Zajac, M.; Kucharski, R.; Grabianska, K.; Gwardys-Bak, A.; Puchalski, A.; Wasik, D.; Litwin-Staszewska, E.; Piotrzkowski, R.; Z Domagala, J.; Bockowski, M.
Abstract: Recent progress in ammonothermal technology of bulk GaN growth in basic environment is presented and discussed in this paper. This method enables growth of two-inch in diameter crystals of outstanding structural properties, with radius of curvature above tens of meters and low threading dislocation density of the order of 5 × 10 4  cm −2 . Crystals with different types of conductivity, n-type with free electron concentration up to 10 19  cm −3, p-type with free hole concentration of 10 16  cm −3, and semi-insulating with resistivity exceeding 10 11  Ω cm, can be obtained. Ammonothermal GaN of various electrical properties is described in terms of point defects present in the material. Potential applications of high-quality GaN substrates are also briefly shown.